Current Status and Trends of Automotive Lithium-ion Batteries - Makoto UE (Electrochemistry)
Current status and trends of automotive lithium-ion batteries are reviewed from the viewpoints of important performance by showing their energy density, power density, life, safety, operating temperature range, and cost in current electric vehicles around the world. This kind of information is very limited and useful, because many battery researchers in academia are unaware of the current situation of automotive lithium-ion batteries, and they can evaluate the performance of next generation batteries in comparison with the current lithium-ion batteries.